A CASE REPORT ON VULVAR LIPOMA - Chaithra DM; Gayathri Bhat N V (International Journal of Ayurveda and Pharma Research, 2020)
Lipoma is a benign tumor made of fat tissue. Usually seen in neck, upper back, shoulder, abdomen, buttock. Vulvar lipoma is said to be rare, only few cases have been reported. Usually it is seen between 40 – 60 years, only 2% population are affected with lipoma. Lipoma can be corelated in Ayurveda to Granthi based on its characteristic feature. Due to vitiated Vatadi dosha, Rakta, Meda, Mamsa there will be formation of nodular or glandular swelling which is round, hard in nature is called as Granthi. In this case report based on the content of the mass it can be corelated Medojagranti. Its pathology can be seen in two stages Pakva and Apakva avastha. In Apakva avastha, Shodana is the line of treatment. If it is predominant of Meda (fat) and excision- Chedana is line of treatment in Pakva avastha followed by Dahana karma. Objective: Management of vulvar lipoma. Materials and Methods: A 30 year old female complaining of mass in right vulvar region since 6months, was feeling discomfort while walking and sitting came to OPD of PTSR. Sri Dharmasthala Manjunatheswara college of Ayurveda and Hospital, Hassan. On examination there was a mass measuring 6 x 3x 2cms, which was painless and without any discharge. The patient was advised for admission and was treated surgically by Chedana karma. HPE reports revealed lipomatous polyp. Result: Chedana karma- mass was excised surgically. Conclusion: Based on the content of lipoma it can be correlated to Medojagranti. It was in Vulvar region, large, causing discomfort to the patient so rather than managing with Shamana Aushadi, Shastra karma–Chedana was performed.